2003
DOI: 10.1128/jb.185.6.1841-1850.2003
|View full text |Cite
|
Sign up to set email alerts
|

ARhizobium leguminosarumAcpXL Mutant Produces Lipopolysaccharide Lacking 27-Hydroxyoctacosanoic Acid

Abstract: The structure of the lipid A from Rhizobium etli and Rhizobium leguminosarum lipopolysaccharides (LPSs) lacks phosphate and contains a galacturonosyl residue at its 4 position, an acylated 2-aminogluconate in place of the proximal glucosamine, and a very long chain -1 hydroxy fatty acid, 27-hydroxyoctacosanoic acid (27OHC28:0). The 27OHC28:0 moiety is common in lipid A's among members of the Rhizobiaceae and also among a number of the facultative intracellular pathogens that form chronic infections, e.g., Bruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(82 citation statements)
references
References 54 publications
7
75
0
Order By: Relevance
“…In the case of indeterminate nodules, it is possible that the maintenance of single occupancy symbiosomes results from more intimate contact between the dividing bacterial cell and the PM, whereas the latter determinate process involves detachment of the bacterial and PM cell. In the former case, we have reported that an R. leguminosarum biovar viciae mutant that is defective in the synthesis of the very long fatty acid moiety of its lipid A is also defective in bacteroid formation, and results in multiple occupancy symbiosomes (52,53). It is important to investigate the characteristics of the surface polysaccharides of bacteroids in these and other symbiotic systems in order to be able to fully understand the mechanism of symbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of indeterminate nodules, it is possible that the maintenance of single occupancy symbiosomes results from more intimate contact between the dividing bacterial cell and the PM, whereas the latter determinate process involves detachment of the bacterial and PM cell. In the former case, we have reported that an R. leguminosarum biovar viciae mutant that is defective in the synthesis of the very long fatty acid moiety of its lipid A is also defective in bacteroid formation, and results in multiple occupancy symbiosomes (52,53). It is important to investigate the characteristics of the surface polysaccharides of bacteroids in these and other symbiotic systems in order to be able to fully understand the mechanism of symbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…These mutant bacteria grow slowly, and they are hypersensitive to detergents and low pH (234,235). However, these mutants are nevertheless able to form partially functional nodules in their host plants.…”
Section: Figure 15mentioning
confidence: 99%
“…results in the failure to incorporate the long secondary acyl chain (Figure 13) (234,235). These mutant bacteria grow slowly, and they are hypersensitive to detergents and low pH (234,235).…”
Section: Figure 15mentioning
confidence: 99%
“…Up to now, the most severe impairments in nodulation were reported in mutants deficient in O-chain (73,98). Significance of lipid A in symbiosis remains unclear because most of lipid A mutants show weak phenotypes such as delay and reduced competitiveness for nodulation (93,112) or sometimes no apparent symbiotic lesion (46,111). LPS may contribute to the establishment of symbiosis as a suppressor of plant defense responses because LPS from S. meliloti have been found to suppress defense responses in a host plant Medicago sativa cell culture induced by a yeast elicitor (1).…”
Section: Determinants Of Rhizobium Symbiosismentioning
confidence: 99%
“…The O-antigen is the most variable domain of the LPS, showing strain by strain diversity (35). LPS mutants of rhizobia exhibited extensive levels of symbiotic impairments ranging from complete lack of nodule formation (98), formation of non-nitrogen-fixing nodules devoid of bacteroids (73,74), nodules with less bacteroids and nitrogen fixation (17), abnormally developed bacteroids (19,85), delay in nodulation (50,93,112) to decreased competitiveness (31,50,93). Nevertheless, the majority of the LPS mutants can invade plant tissue more or less, suggesting that LPS is particularly important in later stage of symbiosis.…”
Section: Determinants Of Rhizobium Symbiosismentioning
confidence: 99%